High and Sustained Ex Vivo Frequency but Altered Phenotype of SARS-CoV-2-Specific CD4+ T-Cells in an Anti-CD20-Treated Patient with Prolonged COVID-19 - Leon Cords; Maximilian Knapp; Robin Woost; Sophia Schulte; Silke Kummer; Christin Ackermann; Claudia Beisel; Sven Peine; Alexandra Märta Johansson; William Wai-Hung Kwok; Thomas Günther; Nicole Fischer; et al. (Viruses, 2022)
Here, we longitudinally assessed the ex vivo frequency and phenotype of SARS-CoV-2 membrane protein (aa145–164) epitope-specific CD4+ T-cells of an anti-CD20-treated patient with prolonged viral positivity in direct comparison to an immunocompetent patient through an MHC class II DRB1*11:01 Tetramer analysis. We detected a high and stable SARS-CoV-2 membrane-specific CD4+ T-cell response in both patients, with higher frequencies of virus-specific CD4+ T-cells in the B-cell-depleted patient. However, we found an altered virus-specific CD4+ T-cell memory phenotype in the B-cell-depleted patient that was skewed towards late differentiated memory T-cells, as well as reduced frequencies of SARS-CoV-2-specific CD4+ T-cells with CD45RA− CXCR5+ PD-1+ circulating T follicular helper cell (cTFH) phenotype. Furthermore, we observed a delayed contraction of CD127− virus-specific effector cells. The expression of the co-inhibitory receptors TIGIT and LAG-3 fluctuated on the virus-specific CD4+ T-cells of the patient, but were associated with the inflammation markers IL-6 and CRP. Our findings indicate that, despite B-cell depletion and a lack of B-cell—T-cell interaction, a robust virus-specific CD4+ T-cell response can be primed that helps to control the viral replication, but which is not sufficient to fully abrogate the infection.